2023
DOI: 10.1186/s40360-023-00648-z
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhetinic acid protects against Multidrug-resistant Acinetobacter baumannii-induced lung epithelial cells injury by regulating inflammation and oxidative stress

Abstract: Glycyrrhetinic acid (GA) is a bio-effective component of Licorice. The GA is a monomer and the ingredient is an Oleanane-type pentacyclic triterpenes that has been used as a remedy for years. Due to the abuse of antibiotics, people pay attention to the emergence of Multidrug-resistant Acinetobacter baumannii (MDR-AB). As a conditional pathogen, MDR-AB causes severe infection, endangering human lives. Our previous studies found GA played an important role in Yinhua Pinggan, a Chinese medicine. However, whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Guan et al (2023) has reported that Glycyrrhetinic acid not only shows anti-inflammatory activities but is also able to inhibit the growth of carbapenem-resistant K. pneumoniae. Other studies have also confirmed that Glycyrrhetinic acid can provide protection against Acinetobacter baumannii and P. aeruginosa induced nosocomial infections (Carruthers et al, 2020;Guo et al, 2023).…”
Section: In-vitro Analysismentioning
confidence: 82%
“…Guan et al (2023) has reported that Glycyrrhetinic acid not only shows anti-inflammatory activities but is also able to inhibit the growth of carbapenem-resistant K. pneumoniae. Other studies have also confirmed that Glycyrrhetinic acid can provide protection against Acinetobacter baumannii and P. aeruginosa induced nosocomial infections (Carruthers et al, 2020;Guo et al, 2023).…”
Section: In-vitro Analysismentioning
confidence: 82%
“…Various reports have shown that LPS, an endotoxin produced by Gram-negative bacteria, exerts severe oxidative stress on macrophages owing to excessive ROS production, which activates the inflammatory signaling cascade. Recently, it was discovered that MDR A. baumannii invasion causes lung epithelial cell injury owing to oxidative stress triggered by ROS generation [39]. Therefore, we suspected that the macrophage cell damage caused by CRAB infection may be due to ROS production.…”
Section: Rhamnetin Inhibits Ros Generation In Crab-stimulated Murine ...mentioning
confidence: 99%
“…1 A) 9 11 . PD is also an important component of traditional Chinese medicine compounds, Yinhuapinggan (YHPG) granules used to treat respiratory infections 12 16 . YHPG was composed of six herbs, which had the effect of clearing heat and detoxifying 17 .…”
Section: Introductionmentioning
confidence: 99%